2018
DOI: 10.1371/journal.pone.0197682
|View full text |Cite
|
Sign up to set email alerts
|

Association of ocular, cardiovascular, morphometric and lifestyle parameters with retinal nerve fibre layer thickness

Abstract: BackgroundGlaucoma is a neurodegenerative disease, leading to thinning of the retinal nerve fibre layer (RNFL). The exact influence of ocular, cardiovascular, morphometric, lifestyle and cognitive factors on RNFL thickness (RNFLT) is unknown and was analysed in a subgroup of the Gutenberg Health Study (GHS).MethodsGlobal peripapillary RNFLT was measured in 3224 eyes of 1973 subjects (49% female) using spectral-domain optical coherence tomography (SD-OCT). The association of age, sex, ocular, cardiovascular, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 24 publications
3
39
2
1
Order By: Relevance
“…The influence of lipid levels on retinal layer thickness has been previously investigated. A subgroup analysis of the Gutenberg Health Study (GHS) examining the influence of various factors on retinal nerve fiber layer (RNFL) thickness in a total of 1973 subjects showed no significant association between RNFL thickness and lipid levels in the multivariable model 34 . Similarly, the MIPH Eye&Health Study -investigating potential determinants of peripapillary RNFL thickness -found no association between the latter and lipid levels 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The influence of lipid levels on retinal layer thickness has been previously investigated. A subgroup analysis of the Gutenberg Health Study (GHS) examining the influence of various factors on retinal nerve fiber layer (RNFL) thickness in a total of 1973 subjects showed no significant association between RNFL thickness and lipid levels in the multivariable model 34 . Similarly, the MIPH Eye&Health Study -investigating potential determinants of peripapillary RNFL thickness -found no association between the latter and lipid levels 35 .…”
Section: Discussionmentioning
confidence: 99%
“…26 Additionally, another study reported a negative relationship between axial length and pRNFL thickness in a population-based cohort study. 27 It seemed that the elongation of the globe leads to mechanical stretching and thinning of the retina. In the present study, axial length did not show a significant result associated with pRNFL reduction in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The following parameters were included in the multivariable model because they were considered to be associated with the pRNFL based on the medical literature [23][24][25] and were judged as being potentially associated with birth weight: (1) age, (2) sex, (3) axial length, (4) age-related macular degeneration, and (5) glaucoma (ISGEO definition).…”
Section: Covariatesmentioning
confidence: 99%